PENGARUH PEMBERIAN MAKANAN TAMBAHAN BERBAHAN PANGAN LOKAL TERHADAP STATUS GIZI PADA BALITA GIZI KURANG (12-56 BULAN) DI KELURAHAN KEDUNG ASEM KOTA PROBOLINGGO - Devianti, Dian Ika; Retnaningsih, Reny; Ilmiah, Widia Shofa (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
Indonesia including 17th countries which have nutritional problems, less intake of toddlers is one of reason malnutrition. The government efforts to manage of nutritional problems in toddlers is by providing supplementary food and this activity have done by Wonoasih Public Health since 2010th, but at 2023th change with Supplementary Foof from Local Food Ingredients in snack form. This study aims to understand the impact of supplementary food made from local ingredients on the nutritional status of undernourished toddlers (ages 12-56 months) in Kedung Asem, Probolinggo City. The research design was pra eksperimental design with pre post test design which is done in 90th days from Desember 1th, 2023 until February 29, 2024. The study focuses on all malnourished toddlers in Kedung Asem Sub-district, involving 16 respondents. A simple random sampling method was used. Data collection included recording the toddlers' weight and height over one month using monitoring sheets. The data were analyzed using the Wilcoxon Signed Ranks Test to determine the differences between paired samples. The study examined the nutritional status of toddlers (12-56 months) before and after receiving supplementary food (PMT). Initially, all 16 respondents (100%) were malnourished. Over 90 days, there was an improvement: 11 respondents (68%) remained malnourished, while 5 respondents (32%) attained good nutritional status. The Wilcoxon Signed Ranks Test showed an Asymp. Sig (2-tailed) value of 0.001, indicating a significant difference in nutritional status pre- and post-intervention (p-value < 0.05). Thus, H1 was accepted, and H0 was rejected. The study concluded that local food-based supplementary feeding positively impacted the nutritional status of undernourished toddlers in Kedung Asem Sub-district, Probolinggo City, suggesting that such interventions should be continued by Public Health authorities as a measure to combat undernutrition. toddlers.